APPLICATION OF THE “BANTER, LANYAH, 10” METHOD TO THE PROCESS OF MEMORIZING THE QUR’AN FOR BAYT TAHFIDZ AL-QUR’AN MAULANA MALIK IBRAHIM ISLAMIC STATE UNIVERSITY MALANG STUDENTS (International Conference on Social and Islamic Studies, 2022)
The background of this research is that many students have difficulty in memorizing the Qur’an at university, both in adding or maintaining the memorization. The cause of this difficulty is many hours of studying on campus, assignments, and the student’s participation in campus activities such as organizations, which drains time and lowers the level of concentration on the Qur’an memorization process. This study aims to describe the effectiveness of the “Banter, Lanyah, 10” method in helping students to add and maintain their memorization, using qualitative research methods. The subjects of this study were students in Bayt Tahfidz Al-Qur’an UIN Malang class of 2019. Data collection was carried out using observation, interview and test techniques. The results of this study are that more than 50% of respondents experienced an increase in memorizing repetition (murojaah) with an increase of at least 2 juz to be more fluent, and more than 40% of respondents experienced an increase in the addition of memorization (ziyadah) with a total of more than 1 juz during  minimum period of 1 year.  From the data obtained, it can be concluded that the use of the "Banter, Lanyah, 10" methodmethod is an effective method for helping students memorize on campus level.